2016
DOI: 10.1021/acs.jproteome.6b00103
|View full text |Cite
|
Sign up to set email alerts
|

Interactome Analysis of the NS1 Protein Encoded by Influenza A H1N1 Virus Reveals a Positive Regulatory Role of Host Protein PRP19 in Viral Replication

Abstract: Influenza A virus, which can cause severe respiratory illnesses in infected individuals, is responsible for worldwide human pandemics. The NS1 protein encoded by this virus plays a crucial role in regulating the host antiviral response through various mechanisms. In addition, it has been reported that NS1 can modulate cellular pre-mRNA splicing events. To investigate the biological processes potentially affected by the NS1 protein in host cells, NS1-associated protein complexes in human cells were identified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 50 publications
1
42
1
Order By: Relevance
“…Previous studies from our laboratory have shown that the 14-3-3 protein also binds to the severe acute respiratory syndrome (SARS) coronavirus nucleocapsid (N) protein [79]. This binding allows the regulation of nucleocytoplasmic shuttling of N protein in a phosphorylation-dependent manner.…”
Section: Role Of 14-3-3 Family In Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from our laboratory have shown that the 14-3-3 protein also binds to the severe acute respiratory syndrome (SARS) coronavirus nucleocapsid (N) protein [79]. This binding allows the regulation of nucleocytoplasmic shuttling of N protein in a phosphorylation-dependent manner.…”
Section: Role Of 14-3-3 Family In Rna Virusesmentioning
confidence: 99%
“…The apoptosis pathway, cell cycle, cell signaling, ubiquitin ligase, and nucleocytoplasmic shuttling are the most common pathways which were usurped and manipulated by the viruses to favor their replication. [78,79] We also elaborate on all the signaling pathways that are manipulated by 14-3-3-virus interactions (Figure 3). It is interesting to note that cellular proteins are essential for the replication of many RNA and DNA viruses, and may serve as viable targets for treating viral infections.…”
Section: Role Of 14-3-3 In Dna Virusesmentioning
confidence: 99%
“…In addition to serving as an IFN antagonist, accumulating evidence indicates a modulatory role of NS1 on cellular and viral gene expression (Falcon et al, 2004;Wang et al, 2010;Kuo et al, 2016b). We exploited a mini-genome reporter assay to determine the possible role of NS1 on viral RdRp activity.…”
Section: Effect Of Non-structural Protein 1 On Viral Genome Activationmentioning
confidence: 99%
“…The m/z scan range for the MS scans was set as 350-2000 Da, and the ion signal of (Si (CH 3 ) 2 O) 6 H + at m/z 445.120025 was used as a lock mass for internal calibration. To increase identification coverage, the precursor ions selected for MS/MS analysis were dynamically excluded for 180 s [46][47][48] .…”
Section: In-gel Digestion and Mass Spectrometric Analysismentioning
confidence: 99%